To the Reconstruction of the Ancient Karelian Anthroponymicon - Denis V. Kuzmin (Вопросы ономастики, 2020)
The article considers a number of issues related to personal pre-Christian names of the Karelian population falling into two major groups: native non-Christian names and non-calendar names of Russian origin. The author notes that the corpus of historical Karelian names is currently incomplete and little studied. This is due to several reasons, starting with the scarcity of documentary evidence featuring names of this type. In this regard, the study is primarily focused on identifying the possible ways and sources of reconstruction of the pre-Christian Karelian anthroponymicon. According to the author, some of it can be restored using folklore texts and some language sources thought as close to the pre-Christian Karelian anthroponymy. These are, firstly, Russian non-calendar names borrowed by the Karelians through contacts with the Russian population. Secondly, these are the names of the Sami, previous inhabitants of territories bordering modern Karelia, who were using Karelian names extensively, as historical documents indicate. Zoonymy, particularly cattle nicknames, is the third probable source for the reconstruction of the ancient Karelian name system. This is supported by the fact that during the transition of the Karelian population from the pagan to the Christian beliefs, the original names did not disappear but switched to a lower “everyday” level. The fourth source represented by folk forms of Karelian Christian names receives particular attention. Many of these forms are homonymous or consonant with Karelian common nouns, for example, the names of animals and birds (Petra — ‘Pyotr,’ cf. Kar. Petra — ‘deer’) and the words that characterize a person (Makki — ‘Makar,’ cf. Kar. Makki — ‘cheat, swindler’). This suggests that the corresponding tokens could be used as household names or nicknames. The fifth source named by the author is modern Karelian nicknames, some of which could also act as regular names.